Sustained Loss of Bdnf Affects Peripheral but Not Central Vestibular Targets - Elliott, Karen L.; Kersigo, Jennifer; Lee, Jeong Han; Yamoah, Ebenezer N.; Fritzsch, Bernd (Frontiers in Neurology, 2021)
The vestibular system is vital for proper balance perception, and its dysfunction contributes significantly to fall-related injuries, especially in the elderly. Vestibular ganglion neurons innervate vestibular hair cells at the periphery and vestibular nuclei and the uvula and nodule of the cerebellum centrally. During aging, these vestibular ganglion neurons degenerate, impairing vestibular function. A complete understanding of the molecular mechanisms involved in neurosensory cell survival in the vestibular system is unknown. Brain-derived neurotrophic factor (BDNF) is specifically required for the survival of vestibular ganglion neurons, as its loss leads to early neuronal death. Bdnf null mice die within three weeks of birth, preventing the study of the long-term effects on target cells. We use Pax2-cre to conditionally knock out Bdnf, allowing mice survival to approximately six months of age. We show that a long-term loss of Bdnf leads to a significant reduction in the number of vestibular ganglion neurons and a reduction in the number of vestibular hair cells. There was no significant decrease in the central targets lateral vestibular nucleus (LVN) or the cerebellum at six months. This suggests that the connectivity between central target cells and other neurons suffices to prevent their loss despite vestibular hair cell and ganglion neuron loss. Whether the central neurons would undergo eventual degeneration in the absence of Bdnf remains to be determined.